Using Extract of The Cinnamon (Cinnamomum burmanni) Toward Quality from Nata de Coco Beverages - Dian Trinsiska Anggraini; Elly Purwanti; Wahyu Prihanta (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2015)
Skin of the Cinnamon (Cinnamomum burmanni) is a spice plant, the Cinnamon can used as natural preservative, and substance addititon of food. The Cinnamons can used as a food preservative because it has antimicrobial activity, so it can inhibit the growth of bacteria and fungi. Content compounds of the Cinnamon is volatile oil that is mainly cinnamaldehyde, polyphenols and antioxidants which is characteristic of are bactericidal and fungistatic. The purpose of this study was to determine the effect of various concentrations of the Cinnamons and determine the best concentration of the number of bacterial colonies, storability and the organoleptic of the Nata de Coco beverages. This type of research is True Experiment Design and design used is The Posttest Control Group Design, that is research with the treatment, and control replicates. The study design using a Completely Randomized Design (CRD), with 7 treatments (0%, 5%, 10%, 15% , 20%, 25% dan 30%) and repeated 4 times. The population in this study is at the Nata De Coco’s Substract beverages. Sample of this study is Nata de Coco taken from Pusbang Biotek Tegalgondo village, Malang city. Data were analyzed by Anova 1 factor and followed with Duncan’s test. The results showed that there is effect of various concentration of the Cinnamon to the number of bacterial colonies, storability and the characteristic organoleptic of Nata de Coco beverages. Duncan test results for a number of bacterial colonies, the best concentrations for inhibiting is 30% that are below SNI (1 x 104), whereas the best concentration for the storability is 30% which last up to 5 days. Based on the organoleptic test, preferred aroma is 5% of concentration, preferred color is 10% of concentration, and preferred flavor is 5% of concentration.  Keywords : Exstract Cinnamons, Nata De Coco, Storability, Number of Bacterial Colonies